Presenting an innovative business model based on collaborative, online platforms in the era of the fifth industrial revolution - Rostamzadeh , Reza; Monjezi, Iraj; Isavi, Hero; Šaparauskas, Jonas; Turskis, Zenonas (Transformations In Business & Economics, 2025)
In the framework of the rapid technological evolution that is characteristic of the Fifth Industrial Revolution, digital platforms serve as an indispensable driver for business innovation and sustainable development. This is largely due to their ability to potentially merge human ingenuity with advanced technology. The explosively expanding platform-based sharing economy has fundamentally disrupted traditional economic frameworks and regulatory environments both within nations and globally. The present study employs the meta-synthesis methodology to develop a framework for comprehending platform-centric business operations. This has been conducted via an inductive approach to qualitative meta-synthesis as propounded by Sandelowski and Barroso, integrated with a systematic review process. The researchers extracted the relevant literature from Google Scholar and Web of Science, supplemented by manual searches of relevant journals and their citation networks. Following a thorough review of the 454 source documents, the authors narrowed down to 69 academic articles. The data analysis was a multi-layered process in which the primary coding, axial coding, and selective coding of the research results were conducted. The conclusions that can be made from this work underline the key factors and their relationships, which are critical for successful platform business design. Consequently, they provide valuable guidance for both scholars and practitioners within the digital economic context.